Revisiting Capuchin Monkeys (Cebus capucinus) and the Ancient Maya - Mary Baker (Revue de Primatologie)
Two genera of nonhuman primates, howler monkeys (Alouatta palliata and A. pigra) and spider monkeys (Ateles geoffroyi) currently reside throughout the area inhabited by the modern Maya. Michael Coe (1978, 1989) suggested that the Classic Maya (A.D. 300-900) associated these monkeys, especially howlers, with the arts exemplified in the Quiche Maya creation myth, the Popol Vuh, and in depictions of monkey‑men scribes on Late Classic (A.D. 550‑900) ceramics. Originally refuted by Baker (1992), this paper reevaluates the evidence from both papers, taking an ethnoprimatological, four‑field approach and integrating content from cultural, biological, linguistic and archaeological anthropology to discuss evidence that capuchin monkeys (Cebus capucinus) were also found within the Maya region in ancient times. It is proposed, based on interspecific comparison of morphological and behavioral characteristics and linguistic data, that capuchin monkeys are also represented in depictions of monkey scribes. Although much of the previous literature has focused on the name Hunbatz to determine which monkeys are being represented, it is suggested herein that the term k’oy should be used instead.